Response of narrowband ultraviolet-B phototherapy combined with superoxide dismutase antioxidant cream in the management of non-segmental vitiligo - Muchamad Apriyanto; Hanan Asrafi Noviandari; Niken Indrastuti; Arief Budiyanto (Published by Universitas Gadjah Mada, 2025)
Vitiligo is a skin depigmentation disorder characterized by the loss of melanocyte function. The oxidative stress theory plays a role in the occurrence of vitiligo. Narrow band ultraviolet B (NB-UVB) phototherapy can be combined with other therapies to accelerate skin repigmentation. A 47 yo woman presented to the dermatology and venereology outpatient clinic in Dr. Sardjito General Hospital, Yogyakarta with a chief complaint of white patches on her face, neck, chest, and hands that had persisted for 11 yr. The patient had previously received NB-UVB phototherapy and a calcineurin inhibitor cream, but the symptoms persisted. Significant repigmentation of the lesion area was achieved after NB-UVB phototherapy combined with superoxide dismutase (SOD) antioxidant cream. NB-UVB phototherapy plays a role in immunomodulation, biostimulation, and reducing oxidative stress. The SOD helps clear superoxide radicals, preventing damage to melanocytes. The combination of NB-UVB phototherapy and antioxidant cream can be considered a treatment option for vitiligo.